Electrochemically amplified molecular beacon biosensor for ultrasensitive DNA sequence-specific detection of Legionella sp - Rai, Varun (2013)
An electrochemically amplified molecular beacon (EAMB) biosensor is constructed using thiolated hairpin DNA-ferrocene probes on gold electrode. The switching from “on” to “off” states of individual probes in the presence of complementary DNA target influences the electrode potential, besides the current, owing to changes in surface density of the electroactive hairpin DNA-ferrocene probes. The EAMB biosensor demonstrates linear range over 8 orders of magnitude with ultrasensitive detection limit of 2.3 × 10−14 M for the quantification of a 21-mer DNA sequence. Its applicability is tested against PCR amplicons derived from genomic DNA of live Legionella pneumophila. Excellent specificity down to one and three nucleotides mismatches in another strain of L. pneumophila and a different bacterium species, respectively, is demonstrated.